PENINGKATAN KOMPETENSI SISWA SMK GELORA JAYA NUSANTARA MELALUI PELATIHAN KONFIGURASI ROUTER DAN VLAN - Jamaluddin, Jamaluddin; Harianja, Eva Julia G.; Purba, Eviyanti Novita; Perangin-angin, Resianta; Purba, Mufria J.; Nainggolan, Rena; Lumbantoruan, Gortap; Hutapea, Marlyna I.; Siringoringo, Rimbun; Simamora, Roni J.; Saragih, Rijois I. E.; Zalukhu, Delianus; Panjaitan, Calvin Nicolas; Marpaung, Flora; Sitorus, Hegi Audria (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
This community service activity is an implementation of the tridharma of higher education to provide knowledge to students of SMK Gelora Jaya Nusantara, especially class XI students majoring in network computer engineering (TKJ). The material provided is router configuration and virtual LAN, this material is useful for participants, because it is one of the topics in the competency exam. This service activity starts from the preparation stage carried out by the team and is carried out on June 20, 2023 in the computer laboratory of SMK Gelora Jaya Nusantara. This service activity was carried out in collaboration with the Program Studi D3 Manajemen Informatika dan Komputerisasi Akuntansi with SMK Gelora Jaya Nusantara.